Tipping and the effects of segregation - Anders Böhlmark; Alexander Willén (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
We examine the effect of ethnic residential segregation on short- and long-term education and labor market outcomes of immigrants and natives. Our identification strategy builds on the one-sided tipping point model, which predicts that neighborhood native population growth drops discontinuously once the immigrant share exceeds a certain threshold. After having identified a statistically and economically significant discontinuity in native population growth at candidate tipping points in the three metropolitan areas of Sweden between 1990 and 2000, we show that these thresholds also are associated with a discontinuous jump in ethnic residential segregation. We exploit these thresholds to estimate the intent-to-treat effect of tipping. We find modest adverse education effects among both immigrants and natives. These effects do not carry over to the labor market.
Keywords: J15; J16; R23; 330; residential segregation; education; labor market; regression discontinuity